The judicial sector in Latin America and the Caribbean: Elements of reform (PDF, 5.2 Mb) - (:unkn) unknown (My University, 2016)
This paper proposes a program for judicial reform which specially addresses the main factors affecting the quality of court services, its monopolistic nature and the resultant inefficiency. The reform program also addresses the economic and legal causes at the root of an inefficient and inequitable judiciary.